Some fishing and biological aspets of crocodile shark Pseudocarcharias kamoharai (Matsubara, 1936) in tuna longline in Indian Ocean - Prawira A. R. P. Tampubolon; Dian Novianto; Abram Barata (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
Crocodile shark, Pseudocarcharias kamoharai (Matsubara 1936) is one of the non-target species which is caught by tuna longlines. This shark is the discards fish in tuna longline fisheries and only their liver are utilized. The aims of this research were to determine some aspects relating to the fishing (fishing areas and hook rate) and biological aspect (size distribution and sex ratio) of the crocodile shark. The data were collected directly via observation in tuna longline commercial fishing vessels based in Palabuhanratu, Cilacap and Benoa. The observations were carried out from February 2012 to October 2014 in Indian Ocean. The crocodile sharks were caught at 6o44'42